Revolutions as organizational change : the Communist Party and peasant communities in South China, 1926-1934 - Zhang, Baohui (Hong Kong University Press, 2016)
By comparing peasant revolutions in Hunan and Jiangxi between 1926 and 1934, this book offers a new organizational perspective on peasant revolutions. Utilizing newly available historical materials in the People's Republic of China in the reform era, it challenges the established view that the great Chinese revolution of the twentieth century was a revolution 'made' by the Chinese Communist Party (the CCP).